Production of D-Allose From D-Allulose Using Commercial Immobilized Glucose Isomerase - Choi, Mi Na; Shin, Kyung-Chul; Kim, Dae Wook; Kim, Baek-Joong; Park, Chang-Su; Yeom, Soo-Jin; Kim, Yeong-Su (Frontiers in Bioengineering and Biotechnology, 2021)
Rare sugars are regarded as functional biological materials due to their potential applications as low-calorie sweeteners, antioxidants, nucleoside analogues, and immunosuppressants. D-Allose is a rare sugar that has attracted substantial attention in recent years, owing to its pharmaceutical activities, but it is still not widely available. To address this limitation, we continuously produced D-allose from D-allulose using a packed bed reactor with commercial glucose isomerase (Sweetzyme IT). The optimal conditions for D-allose production were determined to be pH 8.0 and 60°C, with 500 g/L D-allulose as the substrate at a dilution rate of 0.24/h. Using these optimum conditions, the commercial glucose isomerase produced an average of 150 g/L D-allose over 20 days, with a productivity of 36 g/L/h and a conversion yield of 30%. This is the first report of the successful continuous production of D-allose from D-allulose by commercial glucose isomerase using a packed bed reactor, which can potentially provide an economical production system for industrial applications of D-allose.